INTERNATIONAL TREATIES AND BRAZILIAN LAW (CIPEEX, 2025)
This paper examines how the laws of other countries interact with Brazil's legal system, assessing how they are brought into the country, their importance in the law, and their practical application. First, it examines the constitutional framework for bringing treaties into the country; this requires their approval by the National Congress and ratification by the President. The research uses a descriptive and analytical approach, based on doctrine and jurisprudence, especially the firm understanding of the Supreme Federal Court. It highlights the special status of international treaties related to human rights, which receive equal status to constitutional amendments when approved in two rounds with a favorable vote of three-fifths of each house of Congress. Furthermore, it examines the jurisprudence regarding the hierarchy of other treaties, which are in a supralegal position, above ordinary laws but below the Constitution. The results show that Brazil's approach to treaties strengthens the dialogue between international law and domestic law, enabling greater effectiveness in the protection of rights and international cooperation. The conclusion is that the proper application of international treaties by the Brazilian legal system represents a democratic and legal advance, contributing to the country's integration into the international system.
Keywords: International Law; Constitutional Law; International Treaties; Normative Hierarchy